Identifying Work-Related Internet’s Uses—at Work and Outside Usual Workplaces and Hours—and Their Relationships With Work–Home Interface, Work Engagement, and Problematic Internet Behavior - Vayre, Emilie; Vonthron, Anne-Marie (Frontiers in Psychology, 2019)
Many studies have analysed the uses of information and communication technologies (ICT) for work, with some focusing on use at the office and others on use outside the traditional workplace and workday. However, there is little research encompassing all work uses of ICTs, both in and out of the office, and on the ways in which they affect employees’ attitudes toward their work and quality of life. Thus, the present study aims to: a) explore the links between intensity, places and time periods of using the Internet for work; b) examine whether Internet uses for work are related to the perceived impact of work on personal life, work engagement and Internet addiction. An empirical study was conducted based on a questionnaire survey of 502 executives. We measured their use of the Internet for business purposes both in and outside of the standard workday/workplace; the perceived impact of work on their personal life; their work engagement; and their relationship to the Internet. Four categories of Internet use for work were identified (Cluster analysis). They differed with respect to intensity, places, and time periods dedicated to Internet uses (at standard workplace, at home, while travelling; during a typical workday, a day off or vacation). The results obtained from Multinomial Logistic Regression show that technological devices provided by the employer and personal uses of the Internet are related to the intensity, places and time periods of executives’ work-related Internet uses. Furthermore, ANCOVAs reveal that high-intensive, extensive and porous Internet uses for work appear to foster the permeability between work and personal life, diminish managers’ dedication and vigour at work, and favour Internet addiction. Based on these findings, we discuss the importance of the 'right to disconnect' and prevention programmes regarding Internet uses, two major issues which attract the attention of organizations as well as public health authorities.